Dysexecutive syndrome and cerebrovascular disease in non-amnestic mild cognitive impairment: a systematic review of the literature - Felipe Kenji Sudo; Carlos Eduardo Oliveira Alves; Gilberto Sousa Alves; Letice Ericeira-Valente; Chan Tiel; Denise Madeira Moreira; Jerson Laks; Eliasz Engelhardt (Dementia & Neuropsychologia)
ABSTRACT Objective: Non-amnestic dysexecutive Vascular Mild Cognitive Impairment (VaMCI) may represent preclinical Vascular Dementia (VaD). The aim of this study was to summarize the clinical, neuropsychological and neuroimaging aspects of VaMCI; and to assess its patterns of progression to dementia. Methods: Searches were made in the ISI Web of Knowledge, PubMed and Lilacs databases, using the terms "mild cognitive impairment" and "executive function". Altogether, 944 articles were retrieved. Results: VaMCI cases had poorer performances on fronto-executive tasks, a higher prevalence of stroke, presence of periventricular and profound white matter hyperintensities on MRI images, as well as more extrapyramidal signs and behavioral symptoms. Executive dysfunction might be associated with disconnection of fronto-parietal-subcortical circuits. Progression to dementia was associated with baseline deficits in executive function, in simple sustained attention and language, and large periventricular WMH. Discussion: VaMCI develops with impairment in non-memory domains and subcortical white matter changes on MRI images, which are consistent with clinical and neuroimaging findings in VaD.